The extent of the ability and readiness of hospitals in Amran Directorate in Yemen to face and prevent outbreaks of Coronavirus disease (COVID-19) - A field study - Qatinah, Mohammed Ali; Al- Omari, Rehab Qayed; Al- Hajli, Nouria Saleh; Al- Bajal, Amal Abed (Journal of medical and pharmaceutical sciences, 2020)
The World Health Organization has classified the Coronavirus as a global pandemic (cataclysm), and thus an outbreak of this epidemic that has struck the world's largest economies will be disastrous in Yemen.The purpose of the study: The current study aims to measure the ability and readiness of Amran Directorate hospitals and its employees to face and prevent outbreaks of Coronavirus (COVID-19). Research methodology: A descriptive study was conducted between January and May 2020, with a sample of 227 people from the health team and administrators in Amran Directorate hospitals. The study collected data by using a questionnaire that consisting of two parts: a part of the data relating to the demographic properties, the second part of the collection of data related to the measure of the readiness. Main results: In terms of the availability of testing tools and solutions, they are not available in Amran Directorate hospitals (94.7%) (94.3% (, and there is a large shortage of remote temperature measuring devices(74.4% (, respirators (85.5% (, and the number of beds(83.7% (in hospitals. Recommendations: The study recommends that there is a need to equip Amran Directorate hospitals and provide them with all the devices, equipment, tools and special requirements to confront the Coronavirus and prevent the spread, as well as work on training and rehabilitation of their workers to deal with infected and suspected of being infected with the Coronavirus.
Keywords: Corona virus; Amran district hospitals; hospital readiness